Using Plasma and Prothrombin Complex Concentrates - Levy, Jerrold H.; Ghadimi, Kamrouz; Waldron, Nathan H.; Connors, Jean M. (Seminars in Thrombosis and Hemostasis, 2020)
Surgical patients, following procedural interventions or traumatic injury, often bleed due to ongoing blood loss or coagulopathy. Volume resuscitation and transfusion management are critical for the massively bleeding patient. While transfusions may correct coagulopathy, they carry multiple risks including circulatory overload and transfusion-related acute lung injury. Factor concentrates, specifically prothrombin complex concentrates (PCCs), are often used as part of multimodal therapy for bleeding along with laboratory testing to rapidly assess underlying coagulopathy. Although they are commonly used as part of management algorithms, studies evaluating their efficacy against fresh frozen plasma (FFP) or other potential therapies are needed. Further, PCCs are indicated to treat the coagulopathy associated with non-vitamin K oral anticoagulants in the perioperative setting. The focus of this commentary will be the perioperative use of PCCs, plasma, and FFP.
Keywords: factor concentrates; fibrinogen; fresh frozen plasma; hemorrhage; plasma; prothrombin complex concentrates